Halal supply chain integrity : concept, constituents and consequences - Majid, Zawiah Abdul; Shamsudin, Mohd Farid; Abdul Rahman, Nor Aida (New York, NY : Routledge, 2023)
"The market and demand for Halal goods and services is ever increasing and, with it, the importance of supply chain integrity. Integrity from the perspective of Halal logistics service providers is a prerequisite of Halal compliance. This book provides a unique overview of Halal supply chain integrity (HSCI) using examples from Malaysia. The book carefully addresses and simplifies the issue of integrity in Halal logistics and supply chain. It gathers findings from a Halal supply chain integrity study from the leading country in Halal, Malaysia, to shed light of current issues, developments and future trends on the theory and practice of Halal in the logistics sector. In particular, the book discusses factors such as Halal quality assurance, trust and commitment, and halal assets specificity. This will be a useful reference for researchers, scholars and upper-level students who wish to understand Halal logistics and supply chain management and the importance of protecting integrity of Halal services and products"--
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics; Halal food industry -- Marketing; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Industries / Transportation; BUSINESS & ECONOMICS / Distribution